2021
DOI: 10.1016/j.nrleng.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the forgotten pandemic: follow-up of neurocognitive disorders during lockdown in Argentina

Abstract: Introduction Health systems in numerous countries around the world are suffering a serious burden as a consequence of the COVID-19 pandemic. As a result of this situation, the follow-up of such chronic diseases as dementia may be at risk. Similarly, neuropsychiatric complications related to lockdown measures may also be neglected; Argentina’s lockdown has been the longest implemented in Latin America. This study aims to determine the frequency of the different types of medical consultations for ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 8 publications
0
17
0
2
Order By: Relevance
“…Several behavioral and psychological changes due to deprivation or reduced social contact during the pandemic period have also been reported, such as increased anxiety, agitation, and depression [16][17][18]. However, few studies have addressed these impacts on the population with dementia [19][20][21]. A recent study conducted in Italy evaluated neuropsychiatric changes among individuals with dementia and their caregivers during the lockdown period and found that there had been large increases in complaints of these symptoms in about two-thirds of both the patients and the caregivers [22].…”
Section: Discussionmentioning
confidence: 99%
“…Several behavioral and psychological changes due to deprivation or reduced social contact during the pandemic period have also been reported, such as increased anxiety, agitation, and depression [16][17][18]. However, few studies have addressed these impacts on the population with dementia [19][20][21]. A recent study conducted in Italy evaluated neuropsychiatric changes among individuals with dementia and their caregivers during the lockdown period and found that there had been large increases in complaints of these symptoms in about two-thirds of both the patients and the caregivers [22].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies (n = 16) were conducted in the European continent, [13][14][15][23][24][25][26][27][28][29][30][31][32][33][34][35] and the remainder (n = 5) in the Americas. 5,12,[36][37][38] Eight of these studies were cohort studies, and 13 were cross-sectional studies (Table 1). Three studies did not specify the type of dementia.…”
Section: Resultsmentioning
confidence: 99%
“…1) with 21 articles meeting the inclusion criteria (composite sample: N = 7139, range 18–4913, 4.0% MCI, mean age 75.6 ± 7.9 years, 60.0% female). The majority of the studies ( n = 16) were conducted in the European continent, 13–15,23–35 and the remainder ( n = 5) in the Americas 5,12,36–38 . Eight of these studies were cohort studies, and 13 were cross‐sectional studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations